MECHANOCHEMICAL ACTIVATION OF PHARMACEUTICAL SUBSTANCES AS A FACTOR FOR MODIFICATION OF THEIR PHYSICAL, CHEMICAL AND BIOLOGICAL PROPERTIES - SYROESHKIN, A.V.; USPENSKAYA, E.V.; PLETENEVA, T.V.; MOROZOVA, M.A.; MAKSIMOVA, T.V.; KOLDINA, A.M.; MAKAROVA, M.P.; LEVITSKAYA, O.V.; ZLATSKIY, I.A. (International Journal of Applied Pharmaceutics, 2019)
Objective: Study the influence of the mechanical preparation methods (grinding, fluidization) of solid pharmaceutical substances (PS) and herbal raw material on their physicochemical properties and biological activities. Methods: Test substances and solvents-Lactose monohydrate (DFE Pharma, Germany). Sodium chloride, bendazol hydrochloride (all Sigma-Aldrich, USA) and herbal raw material (Callisia fragrans). The dispersity and native structure of pharmaceutical substances were analyzed by several methods: optical microscopy–Altami BIO 2 microscope (Russia); low angle laser light scattering (LALLS) method (Malvern Instruments, UK); Spirotox method–Quasichemical kinetic of cell transition of cellular biosensor Spirostomum ambiguum; Fourier-transform infrared spectroscopy–the analysis in the middle IR region was carried out using an IR Cary 630 Fourier spectrometer (Agilent Technologies, USA). The analysis of dried leaves of C. fragrans before and after mechanical activation was performed using Shimadzu EDX-7000 X-ray fluorescence spectrophotometer without mineralization (Shimadzu, Japan). Results: It was established that the mechanical change, such as dispersion and drying, alters the biological activity of PS and herbal raw materials. The observed increase in the influence of the dispersed substance on the biosensor S. ambiguum is quantitatively estimated from the values of the activation energy (obsEa), which turns to be valued 1,5 (P≤0,05) times more than for the native form substance. In the study of the dependence of the availability of chemical elements K, Ca, Zn on the degree of dispersion of herbal raw materials was established a quantitative 4-fold (P≤0,05) increase in the concentration of elements in mechano-activated raw materials. Conclusion: By the example of the biological model of Spirotox (single-celled biosensor S. ambiguum) and herbal raw materials obtained from C. fragrans, the increase of biological activity of PS at the dispersion of initial preparations was proved.